Characterization of coffee parchment and innovative steam explosion treatment to obtain microfibrillated cellulose as potential composite reinforcement - Raquel S. Reis (Journal of Materials Research and Technology, 2020)
Most by-product wastes of the coffee industry are underutilized, including a fibrous husk that covers the coffee seeds, known as parchment. The present work aims to characterize the parchment fiber and to study the influence of alkaline treatment followed by a steam explosion process assisted by mechanical high shearing to obtain microfibrillated cellulose. The first step of this study was to quantify, using a three-steps methodology, the lignocellulosic constituents present in the parchment. Cellulose, hemicellulose and lignin were identified by Fourier transform infrared spectrophotometry (FTIR) and thermogravimetric analysis (TGA). From these results it was quantified around 22% of cellulose in the parchment. In sequence, alkaline treatment and steam explosion were performed to raise the cellulose content. The novelty of this work was to perform the steam explosion under relatively milder conditions, in order to produce microfibrillated cellulose with a high aspect ratio. It was observed by TGA an improvement in thermal stability and by X-ray diffraction (XRD) an increasing in the crystallinity. Finally, from scanning electron microscopy (SEM) it was verified that cellulose fibrils became more exposed, with diameters reaching micro and nanometric sizes. This ensures a potential for composite reinforcement with microfibrillated cellulose.